Tess of th D'Urbervilles - Hardy, Thomas (London, Penguin Group, 1994)
Set in the bleak, magical Wessex landscape so familiar from Hardy's early work, Tess's cruel story reveals circumstances slowly closing in on her as she attempts to grasp a few moments of happiness with her lover